Pengaruh Ekspor Migas Dan Non Migas Terhadap Cadangan Devisa Di Indonesia Tahun 2014 – 2023 - Heni Mirdania Putri; Fani Muhammad Yamin; Firqi Hidayat; Fiqih Darmawan; Muhammad Kurniawan (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The current global era is pushing countries in the world, including Indonesia, towards international trade. Financing for international trade activities carried out by Indonesia comes from foreign exchange reserves. Foreign exchange reserves are assets owned or saved in the form of foreign currency for foreign financing sources. This research aims to determine the influence of oil and gas and non-oil and gas exports on foreign exchange reserves in Indonesia. The data that researchers used in this research was secondary data for 10 years, starting from 2014 to 2023, obtained from the Central Statistics Agency (BPS). This research uses quantitative methods and the analytical tool used is multiple linear regression analysis using the Eviews10 program. The results of the analysis show that oil and gas and non-oil and gas exports together or simultaneously have a significant effect on foreign exchange reserves in Indonesia. Individually or partially, oil and gas exports have a negative and significant effect on foreign exchange reserves in Indonesia. Meanwhile, non-oil and gas exports partially have a positive and significant effect on foreign exchange reserves in Indonesia.